The use of digital technologies in the Hungarian refugee response - Lengyel-Wang, Z (Refugee Studies Centre, University of Oxford, 2023)
A well-managed Facebook group can mobilise hundreds of thousands of people to maximise peer-to-peer aid, be an effective real-time communication channel between organisations and volunteers, and serve as the focal point of an online refugee aid ecosystem.